Erwinia amylovora affects the phenylpropanoid-flavonoid pathway in mature leaves of Pyrus communis cv. Conférence - Vrancken, K (Plant physiology and biochemistry : PPB, 2013)
Copyright © 2013 Elsevier Masson SAS. All rights reserved.